Transformation of Islamic Religious Education Learning in Facing the Challenges of the Society 5.0 Era - Moh Khoirul Fatihin; Mukmin Mukmin; Muhammad Hilmii Al Fathoni (Institut Agama Islam An-Nawawi Purworejo, 2026)
This study aims to analyze the transformation of Islamic Religious Education (PAI) in the Society 5.0 era in enhancing the quality of learning in higher education and to examine students’ readiness to adopt digital technology in the learning process. This study employed a qualitative approach with a field research design conducted at private universities in East Kalimantan. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the transformation of PAI based on Society 5.0 has been initiated through the integration of digital technology in the learning process while maintaining spiritual and humanistic values. Students demonstrate a good level of readiness in adopting digital technology, reflected in their ability to adapt to digital learning platforms and utilize technology as a learning medium. Furthermore, the successful implementation of this transformation requires strong synergy among lecturers, institutions, and policymakers, particularly in enhancing human resource capacity and providing adequate infrastructure. This study implies the importance of developing adaptive PAI learning models that integrate digital innovation with Islamic values to produce competitive and well-characterized graduates.